دراسـة العلاقة بين تصنيف الدول وفقاً لفجوة الابتكار وتصنيفها وفقاً لمكونات الإطار العام لمؤشّـــــر الابتكـــار العـــالمي GII وانعكاســــها على القطاع المصرفي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
ترتكز الاتجاهات العالمية الجديدة في جميع الصناعات ومنها الصناعة المصرفية بشكل رئيسي على الابتكار. مما يفرض ضرورة مواكبة التطورات الحديثة ضمن الموارد المتاحة، وذلك يخلق ضغوطاً تتعلق بالعديد من العوامل التي تسبب عدم التوازن في الأداء الابتكاري والذي يعبر عنه بمصطلح الفجوة بين مدخلات الابتكار ومخرجاته. ويهدف البحث إلى دراسة العلاقة بين تصنيف الدول وفقاً لفجوة الابتكار، وبين تصنيفها وفقاً لمكونات الإطار العام لمؤشر الابتكار العالمي (المدخلات، المخرجات، الكفاءة، الابتكار)، وانعكاسها على القطاع المصرفي. ولتحقيق هذا الهدف فقد تم جمع البيانات من التقارير الرسمية لمؤشر الابتكار العالمي وذلك ل 31 دولة عالمية وعربية، وكذلك المصارف الأولى والأكثر ابتكاراً وبلغ عددها17 مصرفاً. وقد أظهرت نتائج الدراسة: أن فجوة الابتكار لا تقيّم مستوى الابتكار في الدولة، وإنما ترتبط بقيمة المدخلات والمخرجات وكفاءة الابتكار، كما أنها لا تمثل عائقاً أمام قدرة المصارف على الابتكار. The new global trends Based mainly on innovation, in all industries including the banking industry. This imposes the need to keep abreast of recent developments within the available resources, and it creates a pressure related to many factors that cause the imbalance in innovative performance, which is expressed by term the gap between innovation inputs and outputs. The research aims to study the relationship between the classification of countries according to the innovation gap, and between classified according to the components of the general framework of the Global Innovation Index (input, output, efficiency, innovation), and its impacts on the banking sector. To achieve this goal, data has been collecting from the official reports of the Global Innovation Index for 31 international and Arab countries, as well as the first banks and the most innovative ones, which numbered 17 banks. The results showed that the innovation gap does not evaluate the level of innovation in the country, but links to the value of the input and output and efficiency of innovation, also it does not represent an obstacle to the innovation ability in banks.